The relationship between maximal lactate accumulation rate and sprint performance parameters in male competitive swimmers - Sengoku, Yasuo; Shinno, Anna; Kim, Jaewoo; Homoto, Kenta; Nakazono, Yusaku; Tsunokawa, Takaaki; Hirai, Norimasa; Nobue, Ayaka; Ishikawa, Masaki (Frontiers in Sports and Active Living, 2024)
This study examined the relationship between the maximal lactate accumulation rate (ċLamax) and sprint performance parameters in male competitive swimmers. Seventeen male competitive swimmers volunteered to perform a 20 m maximal front crawl sprint without pushing off the wall from a floating position. ċLamax was determined by the 20-m sprint time and blood lactate measured before and after the 20 m sprint. For the sprint performance parameter, a 50 m time trial with the front crawl swimming stroke was conducted, and the times taken from 0-15 m, 15-25 m, 25-35 m, and 35-45 m were analyzed. A semi-tethered swimming test was conducted to investigate the loadvelocity profile of each swimmer. From the load-velocity profile, theoretical maximal velocity (V0), maximal load (L0) and relative maximal load (r L0) were examined. The slope of the load-velocity profile was also determined. According to the results, ċLamax was significantly correlated with 50 m front crawl performance (r = -.546, p < .05). Moreover, a higher ċLamax was related to faster 0 to 35 m section time. Furthermore, ċLamax significantly correlated with L0 (r = .837, p < .01), rL0 (r = .820, p < .0501), and load-velocity slope (r = .804, p < .0501). ċLamax is a good indicator of 50 m front crawl performance in male swimmers, and higher glycolytic power contributes to the faster time at the beginning of the sprint race. ċLamax could also evaluate the ability of a swimmer to apply force to the water during high-intensity swimming.